Perancangan UI/UX Aplikasi PLATES untuk Perencanaan Gaya Hidup Sehat - I Gede Adrian Satria Pratama S.; I Gusti Agung Gede Arya Kadyanan; Putu Praba Santika (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Public awareness of healthy living in Indonesia continues to grow, yet many still struggle to maintain healthy habits consistently. According to UNICEF (2022), Indonesia's adult obesity rate went from 14.8% in 2013 to 21.8% in 2018. caused by poor diet, physical inactivity, and lack of accessible, personalized nutritional information. To address this, PLATES (Personal Lifestyle Assistant for Tracking Eating and Sustainability) was developed as a mobile application that supports users in maintaining a healthy lifestyle by applying the Design Thinking methodology. Features include a calorie calculator, personalized meal plans, screen time reminders, health challenges, and NutriCamera for scanning food intake. Usability testing with 25 respondents aged 18 to over 51 years yielded an average SUS score of 78.3, indicating good usability across diverse user groups. The findings demonstrate that PLATES can support behavior change and health monitoring effectively. Aiming to guarantee healthy lives and advance well-being for everyone at all ages, the Sustainable Development Goal (SDG) number 3 is in line with this answer.